Construct Validity of Posttraumatic Growth Inventory in the Context of the COVID-19 Pandemic - Ardiana Meilinawati (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2023)
Research that examines the construct validity of Posttraumatic Growth Inventory in the context of the COVID-19 pandemic has never been conducted. This study aimed to test the construct validity of Posttraumatic Growth Inventory (PTGI) on the five dimensions to see the consistency of the PTGI dimensionality structure. Data collection was carried out on 135 COVID-19 survivors, aged 18–40 in Indonesia. Analysis was carried out by confirmatory factor analysis (CFA) and measurement invariance (MI). The results of the analysis proved that PTGI is a measuring instrument that tends to be multidimensional and reliable to be used in Indonesia. All model fit indices met the parameters based on the values of SRMR (<.06), RMSEA (<.10), CFI (>.85), and TLI (>.85). Factor loadings ranged from 0.616 to 0.839 except for item 6 and item 9, which were below 0.6. These low loading factors in item 6 and item 9 were caused by the choice of translated words which tend to be less precise with the dimension being measured. Recommendations related to changes in translated words were explained further in the article as a follow-up to the adjustment of the item statement. Other factors such as personality characteristics, level of self-esteem, and social stigma were also found to be associated with the results of the analysis. MI testing showed that the PTGI model was not influenced by gender in the study sample group.